(untitled) (Costos y Gestión, 2021)
The objective of the study was to identify the components of variable costs with the greatest impact on corn production in the state of Santa Catarina in the 2004/2005 to 2016/2017 harvests. For this, a descriptive research was carried out, conducted through documentary analysis and quantitative approach. For data analysis, a descriptive statistical analysis and multiple linear regression analysis was done to verify the influence of variable costs on corn productivity. Costs related to inputs, mechanics, labor, financial cost, marketing expenses, and other costs were adopted as independent variables in the regression, and productivity was used as the dependent variable. The results indicate that when cultivation is observed in relation to low technology, medium technology, and high technology the variable costs increase, and there is an increase in productivity. The findings refer to the inference that improved productivity is associated with production mechanical investments, and that the use of labor causes lower productivity.